Design methodology for a large scale soil absorption bed for septic tank effluent - Nettles, David L., author; Ward, Robert C., advisor; McWhorter, David B., advisor (Colorado State University. Libraries, 1984)
In recent years there has been much interest expressed by small communities in alternatives to the conventional, centralized chemical-biological wastewater treatment system. One of the alternatives is a large scale soil absorption system. In these systems each home has its own septic tank with the tank effluent conveyed to a single, large absorption field. One of the problems encountered with large scale absorption fields is the buildup of a ground water mound beneath them to the point that insufficient treatment of the effluent is provided. In an attempt to alleviate this problem a model was developed for use in designing a large scale leachfield. The model developed was based on the Rao and Sarma (1981b) model of ground water mound buildup. The model was incorporated into a computer aided design (CAD) package consisting of three major divisions. These divisions were designed to: 1) determine the recharge area needed given the maximum acceptable ground water mound height buildup and the recharge rate, 2) determine the mound height given the recharge area and the recharge rate, and 3) determine the areal extent of the mound given the mound height, the recharge area, and the recharge rate. Testing indicates that the CAD package estimates either the recharge area or the the mound height for a constant recharge rate with reasonable accuracy (within 3% of the actual value). Also, testing indicates that the dosing procedure (applying large effluent volumes for short time periods once or twice daily) used on most large scale leachfields can be approximated by a constant recharge rate applying the same effluent volume per day. The CAD package appears to be well suited to the design of large scale leachfields. Further field testing is needed to establish this fact conclusively. The CAD package will be useful to persons concerned with on-site wastewater treatment for several reasons. 1) It estimates the leach- field area required based on the ground water mound buildup occuring beneath the leachfield. 2) The package can be used to estimate the height of the ground water mound beneath an existing leachfield. 3) The package can also be used to determine what effect the leachfield will have on other ground water influences, such as wells and streams. The CAD package is currently a useful tool that can aid in the design of large scale leachfields. However, the package could be improved by the incorporation of a dynamic recharge component to account for infiltration from precipitation events. Also, additional work on bacterial die-off and nitrogen conversion rates would improve the design by providing a better understanding of the unsaturated zone thickness required for wastewater treatment beneath the leachfield.
Keywords: Sewage disposal, Rural -- Mathematical models; Sewage disposal, Rural -- Data processing